Transposable Element Populations Shed Light on the Evolutionary History of Wheat and the Complex Co‐Evolution of Autonomous and Non‐Autonomous Retrotransposons. Issue 1 (9th December 2021) - Wicker, Thomas; Stritt, Christoph; Sotiropoulos, Alexandros G.; Poretti, Manuel; Pozniak, Curtis; Walkowiak, Sean; Gundlach, Heidrun; Stein, Nils
Abstract: Wheat has one of the largest and most repetitive genomes among major crop plants, containing over 85% transposable elements (TEs). TEs populate genomes much in the way that individuals populate ecosystems, diversifying into different lineages, sub‐families and sub‐populations. The recent availability of high‐quality, chromosome‐scale genome sequences from ten wheat lines enables a detailed analysis how TEs evolved in allohexaploid wheat, its diploids progenitors, and in various chromosomal haplotype segments. LTR retrotransposon families evolved into distinct sub‐populations and sub‐families that were active in waves lasting several hundred thousand years. Furthermore, It is shown that different retrotransposon sub‐families were active in the three wheat sub‐genomes, making them useful markers to study and date polyploidization events and chromosomal rearrangements. Additionally, haplotype‐specific TE sub‐families are used to characterize chromosomal introgressions in different wheat lines. Additionally, populations of non‐autonomous TEs co‐evolved over millions of years with their autonomous partners, leading to complex systems with multiple types of autonomous, semi‐autonomous and non‐autonomous elements. Phylogenetic and TE population analyses revealed the relationships between non‐autonomous elements and their mobilizing autonomous partners. TE population analysis provided insights into genome evolution of allohexaploid wheat and genetic diversity of species, and may have implication for future crop breeding. Abstract : Transposable elements (TEs) populate genomes like individuals populate ecosystems, diversifying into different sub‐families, and sub‐populations. TE population analysis in genomes from ten hexaploid wheat lines is performed. Interestingly, populations of non‐autonomous TEs co‐evolved over millions of years with their autonomous partners, in some cases leading to complex systems with multiple different types of autonomous, semi‐autonomous, and non‐autonomous elements.